UHPLC-HRMS Spectrometric Analysis: Method Validation and Plasma and Urinary Metabolite Identification after Mango Pulp Intake - Cáceres-Jiménez, Salud; Rodríguez-Solana, Raquel; Dobani, Sara; Pourshahidi, Kirsty; Gill, Chris; Moreno-Rojas, José Manuel; Almutairi, Tahani M.; Crozier, Alan; Pereira-Caro, Gema (Journal of agricultural and food chemistry, 2023)
After an acute intake of 300 g of mango purée by 10 subjects, 0 and 24 h urine and plasma samples were analyzed by high-performance liquid chromatography–high-resolution mass spectrometry. The method was first validated for 44 reference polyphenols in terms of linearity, specificity, limits of detection and quantification, intra-day and inter-day precision, recovery, and matrix effects in two biological matrices. After method validation, a total of 94 microbial-derived phenolic catabolites, including 15 cinnamic acids, 3 phenylhydracrylic acids, 14 phenylpropanoic acids, 12 phenylacetic acids, 28 benzoic acids, 2 mandelic acids, 15 hydroxybenzenes, and 5 hippuric acid derivatives, were identified or tentatively identified in urine and/or plasma. These results establish the value of the UHPLC-HRMS protocol and the use of authentic standards to obtain a detailed and accurate picture of mango polyphenol metabolites, together with their phase II conjugated metabolites, in human bioavailability studies.